Crenças sobre o ensino de estratégias de leitura: um estudo exploratório no ensino secundário moçambicano - Companhia, Carlito Antonio (Entrepalavras, 2025)
The present study aims to analyze the beliefs about the teaching of reading strategies of Secondary teachers and students in Mozambique. To this end, the theoretical assumptions of Grabe;Stoller (2002), Sariçoban (2002), Borg (2003) and Govzdenko (2005) were followed within the domain of reading strategies and teachers’ and students’ beliefs. Questionnaires were administered to 60 teachers and 180 students from the provinces of Cabo Delgado, Zambezia, Manica, Inhambane, Maputo-City and Maputo-Province. The results of this study show that, in general, teachers and students tend to have different beliefs about the effectiveness of reading strategies. For this reason, it is proposed to carry out training actions for teachers in order to ensure the systematic teaching of reading strategies in the classroom.